DEVELOPING PREDICTIVE MODELS OF INTERNET SERVICE STRATEGIES - Maxim Yu. Khramov (Статистика и экономика)
Issues related to strategic managementof interactive online services as well as difﬁculties in predicting results of strategies’ implementation were studied in the article. As a result methodological andtechnological solutions were workedout; the solutions are based on usage ofsimulation and particularly based on thecombination of such methods as systemdynamics and agent-based modeling.